IMPROVING STUDENTS’ PRONUNCIATION THROUGH TELL ME MORE PRONUNCIATION SOFTWARE - Trivania Ayulistya (University of Kuningan, 2016)
This research aims at finding out whether using Tell Me More software as media can improve students’ pronunciation at tenth grader in Vocational High School Karya Nasional Kuningan. Pre-experimental design was employed in this research to test the objective theories. Pre-test, post-test and questionnaire were used to collect the data. The data were analyzed by using SPSS 20.0. The t-test result was 0.000. It means that it was lower than 0.05 (0.0000.05) so that the null hypothesis is rejected and alternative hypothesis is accepted. Besides, the mean scores of pre-test and post-test in pre-experimental class were significantly different (4,09 up to 6,02). To confirm the result of this research, questionnaires were also used to describe students’ attitude towards the use of this software in improving their pronunciation. As result, it was found that in affective aspects, there were 63,3% of the students who agreed with the use of Tell Me More Software as media to improve students’ pronunciation. In behavioral aspects, there were 50% of the students who agreed with the use of Tell Me More Software as media. The last in cognitive aspects, there were 52,5% of the students who agreed with the use of Tell Me More Software as media. Based on those results, Tell Me More software can be applied by English teachers in teaching pronunciation since this software is effective to improve students’ pronunciation.Keywords: Tell Me More software, pronunciation, students